Occupational therapy without borders : volume 1: learning from the spirit of survivors - Kronenberg, Frank, ....-; Simó Algado, Salvador, ....-; Werner, David, 1934- (Edinburgh : Elsevier/Churchill Livingstone, 2005)
This landmark text challenges occupational therapists to more fully realize the profession's social vision of a more just society where disability, old age, and other marginalizing conditions and experiences are addressed by involving people in helping themselves to (re)gain the capacity and power to construct their own destinies through their participation in daily life. The book explores the new concept of occupational apartheid - the separation between those who have meaningful, useful occupations and those who are deprived of or isolated from occupation, or who are otherwise constrained in their daily life.
Includes bibliographical references and index.
Keywords: Ergotherapie; Occupational therapy